PENGARUH INTELLECTUAL CAPITAL , FREE CASH FLOW, DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN - Catherine, Augustpaosa Nariman (Jurnal Paradigma Akuntansi, 2020)
This research aims to determine the effect intellectual capital, free cash flow and capital structure toward the financial perfomance. This research uses 75 samples manufacturing companies listed on the Indonesia Stock Exchange in the year of 2016-2018 using Eviews 10. The results of t test indicate that intellectual capital have a negative unsignificant effect on financial performance. Free cash flow have a negative significant effect on financial performance and capital structure have positive unsignificant effect on financial performance. The results of this research indicate that all independent variables simultaneously have a significant effect on dividend policy (F test).